CYBER DETERRENCE BY ENTANGLEMENT: ANALYTIC MODEL OF DETERRENCE BY ENTANGLEMENT AS RESULT OF MUTUAL ASSURED DEBILITATION - AL-AZWANI, Nasser S.; CHEN, Thomas M. (Cyberpolitik Journal, 2019)
It seems that deterrence by punishment as a threat of retaliation has worked in deterring nuclear conflict for decades while in cyber it has not yet. Mutual Assured Destruction was the threat that has played a vital role in stimulating rational thinking for deterring state nuclear adversaries while in cyber space it seems Mutual Assured Disruption reflecting mutual cyber debilitation is going to be the context where cyber deterrence function. Stimulating cyber adversary cooperation is the key to achieve enforcement to the attacker decision not to attack because there is no gain expected via pursuing cyber-attacks. This paper aims to shed the light over the situation of mutual debilitation within cyber space and approve this mutual situation can be as a ground for deterrence by entanglement model between two superpowers. Assuming this shared debilitation within the cyber space of both adversaries will encourage them to prioritize strategy of cooperation rather than confrontation. Entanglement model aim to explain situation of shared strength and at the same time fragility between both actors. Relying on strength will normally consequence ongoing lose while relying fragility will stimulate cooperation reflecting mutual need for maintaining cyber space working with high availability. At certain degree, the model will stimulate cooperation due to share interest between both adversaries.